Augmented screen, triple narrative, and user role: a case study - Sosa-Fernández, Rocío del Pilar (2023)
The present panorama shows a society saturated with images, driven using mobile devices and constant audiovisual consumption. However, no greater skills are achieved in users, but on the contrary, there is evidence of a detriment in the rate of attention and the need for a differentiating product from the wide range of available content. Given this recent uncertainty, the film industry has found a great ally in technology. The existence of technologies such as augmented reality is still in its infancy and raises new questions about the potential for its use in film. In this study, we conducted a case study analysis of the first Disney augmented reality short film, Remembering (Allan-Blitz, 2022). The methodology used focuses on three approaches: audiovisual language, technological viewing and the role of the receiver. The results show the existence of a digital and economic disparity, due to the particularity of the viewing hardware. In addition, the story presents a tripartite narrative; a slower and simpler one with wide shots, a faster and more unstable one where physical and virtual spaces converge, and a last one created by the user as a steadycam. These readings require a more active and present spectator, in a story that lacks the adaptation of audiovisual language to the new form of visualisation, in which the possibilities of time and space provided by these technologies are not taken advantage of.